TİCARET SİCİLİ MÜDÜRLÜĞÜ KARARLARINA İTİRAZ EDEBİLECEK KİŞİLER - (:unkn) unknown (My University, 2017)
Türk Ticaret Kanunu’na göre ilgililer, temsilcileri veya hukuki halefleritescili talep edebilir. Sicil müdürlüğü kararlarına itiraz edebilecek kişilerin ise ilgililerolduğu ifade edilmiştir. İlgililerin kimler olduğu Türk Ticaret Kanunu’nda sayılmamış-tır. Ticaret Sicili Yönetmeliği’nde ise tescili talep edebilecek kişiler sayılmıştır. Fakatsicil müdürlüğü kararlarına itiraz edebilecek kişiler sayılmamıştır. Ticaret sicili aleni birsicildir. Sicil müdürlüğü tarafından alınacak kararlara kimlerin itiraz edebileceği önem-lidir. Bu makalede bu kişilerin kimler olduğu incelenmiştir.

According to Turkish Commercial code, the concerned parties, their representatives or legal successors may request registration. On the other hand it’s mentioned that those who can object to the decisions of the trade registry are the concerned parties. The concerned parties are not specified in the Turkish Commercial Code. Whereas, in the Trade Registry Regulation those who can request registration are specified, but those who can object to trade registry decisions are not. Trade registry is an open registry. Who can object to the decisions of the trade registrar is important. In this article it has been examined who these parties are.
Who can Object to Trade Registry Decisions
Keywords: Hukuk